La piedra del cielo: algunos aspectos de la educación e iniciación religiosa de los príncipes incas - Ziólkowski, Mariusz S. (Pontificia Universidad Católica del Perú. Fondo Editorial, 1984)
In this article the author tries to determine what was the specific character of the "information" that the Sapan, Inka possessed, this quality, earned him his high position in the Inca religious and state hierarchy.

En este arículo el autor trata de determinar cual fue el caracter específico de la "información" que poseía el Sapan, Inka, esta calidad, le valía su alta posición en la jerarquía religiosa y estatal inca.
The stone of the sky: some aspects of the education and religious initiation of the Inca princes
Keywords: Antropología; https://purl.org/pe-repo/ocde/ford#5.04.03